Effect of Heptral on Blood Coagulant Activity in Pancreonecrosis - M. S. Sukach; V. T. Dolgikh (Общая реаниматология)
Objective: to attempt to reduce the hemostatic, detoxifying, and antioxidant dysfunctions of the liver in experimental pancreonecrosis and the degree of pancreatogenic endotoxemia, by using the hepatoprotector heptral. Materials and methods. Experiments were carried out on 142 outbred male rats divided into 3 groups: 1) control (n=20); 2) study (n=69); 3) comparison (n=53). Pancreonecrosis was simulated in the study and comparison groups. In Stage 1, coagulation hemostatic parameters were studied and the levels of low and medium molecular weight substances and the rate of free radical oxidation processes were determined. In Stage 2, five minutes after stimulation of pancreonecrosis, heptral was given in a dose of 11.4 mg/kg to the comparison animals, by studying the same parameters as in the study and control groups. The results were processed using the nonparametric statistical methods. Results. It has been found that hepatic detoxifying and antioxidant functions are impaired and free radical oxidation processes activated within 2 days after simulation of pancreonecrosis. Blood coagulation activity is considerably higher due to activated coagulation factors. Heptral increases the capacity of the liver to synthesize blood coagulation factors, which proves improvement of some of the study parameters of the hemostatic system. Furthermore, its administration preserves the antitoxic function of hepatocytes, as shown by the decreased concentrations of low and median molecular weight substances in plasma and red blood cells. At the same time, there is an increase in antioxidant system activity detectable by chemiluminescence which also testifies that hepatic functional and metabolic impairments are ameliorated. Key words: pancreonecrosis, liver, endotoxemia, hemo-stasis, free radical oxidation, heptral.